Roles of CCAAT/enhancer-binding protein in transcriptional regulation of the human IL-5 gene - Li-Weber, Min; Giaisi, Marco; Krammer, Peter H. (European journal of immunology, 2001)
Abstract Interleukin-5 (IL-5) plays a critical role in the pathogenesis of eosinophil-associated allergic disorders, such as asthma. IL-5 may also play a major role in the development of eosinophilia-associated lymphoproliferative disorders caused by human T lymphotropic virus type?I (HTLV-I). In this study, we have investigated the control mechanisms for IL-5 production and found that ectopic expression of NF-IL6 (C/EBP?) increases endogenous IL-5 mRNA expression. The IL-5 promoter contains four C/EBP consensus sequences. We show here that one of the C/EBP site at ??235 promoter region binds to NF-IL6 protein with high affinity and interacts with NF-IL6 and NF-IL6? (C/EBPδ) in Jurkat T?cells. Mutations within the C/EBP sequence reduced the promoter activity in response to T?cell activation by more than 50?%. In addition, we show that in vivo inducible expression of Tax protein in Jurkat T?cells stably transfected with Tax further increased ionomycin plus phorbol ester stimulated IL-5 promoter activity. The effect of Tax on IL-5 promoter activity was abolished when the C/EBP site was mutated. Thus, the C/EBP site may be also involved in HTLV-I Tax-mediated up-regulation of IL-5 gene expression. Our data suggest that C/EBP proteins may regulate IL-5 gene expression in response to different stimulation signals.
Gesehen am 21.04.2021